Leukocyte telomere length and epigenetic-based mortality risk score: associations with all-cause mortality among older adults - Gao, Xu; Zhang, Yan; Mons, Ute; Brenner, Hermann (Epigenetics, 2018)
Telomere length (TL) has been established as a biomarker of aging and aging-related health outcomes, but showed only a weak or inconsistent association with all-cause mortality in previous epidemiological studies. Recently, an epigenetic 'mortality risk score' (MS) based on whole blood DNA methylation at 10 mortality-related CpG sites has been demonstrated to be strongly related to all-cause mortality at the population level. This study aimed to address the association between TL and this MS, and to assess and compare their associations with all-cause mortality. The MS was derived from the DNA methylation profiles measured by Illumina Human Methylation450K Beadchip and TL was measured by quantitative PCR at baseline among 1517 participants aged 50-75 of the German ESTHER cohort study. In cross-sectional bi- and multivariable analyses, the MS was strongly associated and showed monotonic dose-response relationships with TL (p-values <0.05). However, only the MS but not TL was associated with all-cause mortality during a median follow-up of 12.5 years. After controlling for potential covariates and TL, hazard ratios (95% CI) for all-cause mortality for low, moderate and high levels of the MS defined by 1, 2-5 and >5 CpG sites with aberrant methylation were 2.24 (1.13-4.41), 3.31 (1.76-6.22) and 6.33 (3.22-12.41) compared to a MS of 0, respectively. Our investigation shows that the epigenetic-based MS is strongly associated with TL, a broadly accepted aging biomarker, and at the same time shows much stronger associations with all-cause mortality than the latter.